Effects of aromatherapy with lavender essential oil on sleep quality among retired older adults - Fatemeh Sadat Izadi-Avanji; Sedigheh Miranzadeh; Hossein Akbari; Neda Mirbagher Ajorpaz; Darius Ahmadi (Gonabad University of Medical Sciences, 2019)
Poor sleep quality is one of the most common problems among older adults. Non-pharmacological interventions are considered as a better choice for treatment of sleep problems in older adults. The aim of the present study was to examine the effects of aromatherapy with lavender essential oil on sleep quality in older adults. This single-blind randomized controlled clinical trial was conducted on 100 retired older adults. Participants were divided into two groups using simple random sampling. The intervention group received 2 drops of lavender essential oil and the control group received 2 drops of placebo in a glass of water, during bedtime, for 7 nights. All participants filled out the Pittsburgh sleep quality index before and after the intervention. There was no statistically significant difference between the groups in terms of socio-demographic characteristics and sleep quality score before intervention. A significant difference in sleep quality was observed in the group receiving lavender essential oil compared to the control group 7 nights after intervention. Lavender essential oil has a positive effect on improving older adults' sleep quality.